Lipid levels do not influence the risk of venous thromboembolism - van Schouwenburg, Inge M.; Mahmoodi, Bakhtawar K.; Gansevoort, Ron T.; Muntinghe, Friso L.H.; Dullaart, Robin P.F.; Kluin-Nelemans, Hanneke C.; Veeger, Nic J.G.M.; Meijer, Karina (Thrombosis and Haemostasis, 2012)
Studies on the association between lipid profile and venous thromboembolism (VTE) are inconsistent. This could be caused by classical lipoproteins being inferior to apolipoproteins as markers for VTE risk. Therefore, we examined whether apolipoproteins are more strongly related to VTE than lipoproteins. For this analysis we used the PREVEND prospective community based observational cohort study. Levels of apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), total cholesterol (TC), high-density lipoprotein (HDL), non-HDL, low-density lipoprotein (LDL), triglycerides (TG), lipoprotein(a), ApoB/ApoA1 and TC/HDL ratio were assessed. Subjects with VTE were identified using databases of the national registries of hospital discharge diagnoses, death certificates, and the regional anticoagulation clinic. Out of 7,627 subjects, 110 developed VTE during a median follow-up of 10.5 years. In both univariate and multivariable analyses no significant associations between apolipoproteins and overall VTE were observed. Of the classical lipoproteins, TC, non-HDL, LDL, TG, and TC/HDL ratio were significantly associated with overall VTE in univariate analysis. Significant associations were no longer present in multivariable analysis. TGL and LDL were significantly associated with unprovoked VTE in univariate analysis. After adjustment for age and sex this significance was lost. No significant associations between (apo-) lipoproteins and provoked VTE were found. We conclude that apolipoproteins are not better in predicting VTE risk than the classical lipoproteins. Our population-based cohort study does not show an association between both apolipoproteins and the classical lipoproteins and VTE risk.
Keywords: Venous thromboembolism; apolipoprotein; lipoprotein; lipid